Aplikasi Dashboard Visualisasi Data Calon Mahasiswa Baru mengunakan Metabase - Yumarlin MZ; Jemmy Edwin Bororing; Sri Rahayu; Tan Anugrah Ramadhani (Universitas Hamzanwadi, 2022)
New student data Information systems can be used as a supporting tool to support decisions. Janabadra University is one of the universities in Yogyakarta, the information system for recording transactional data for students is still done simply in the form of text and numbers. The purpose of this research is to design and build a dashboard application for data visualization of prospective students at Janabadra University for new student admissions (PMB). The method used is a business intelligence roadmap with six stages, the stages are (1) justification, (2) planning, (3) business case, (4) design, (5) construction, and (6) deployment which is a reference in the design and construction of a data warehouse using Metabase. The results of this study can build 7 (seven) visualization dashboards are (1) Dashboard of information students grouped based on the total number of PMB registrants, (2) Dashboard of the number of registrants based on the academic year, (3) Dashboard of income from PMB registration based on the payment date, (4) Dashboard of the number of students based on the academic year of each study program, (5) Dashboard of the number of registrants by class, (6) Dashboard of the number of PMB registrants by semester and (7) Dashboard of the number of PMB registrants by study program and class.